An Analysis of UCNS Certified Headache Center Patient Intake Forms. Issue 3 (15th February 2016) - Sharon, Roni; Rayhill, Melissa; Joseph Viknevich,; Charleston, Larry; Mathew, Paul G.
Abstract : Objective: Compare the similarities and differences among headache intake forms from headache centers with United Council of Neurologic Subspecialties (UCNS) accredited headache medicine fellowships in the United States. Patient intake forms establish a first communication with patients. There have been no studies evaluating them at headache centers. Analysis of these forms can provide insight into their content and potential for improvement. Methods: This observational study involved collection and analysis of intake forms from 25 UCNS fellowship accredited headache centers from July 2014 to October 2014. Forms were compared and contrasted in terms of data fields included, response format, and use of validated assessment tools. Results: Forms shared many common elements, yet were highly variable in content, style, scales, and methods of analysis. Twenty percent (5/20) of centers did not have a formal intake form. Forms ranged from 1 to 28 pages. Seventy percent (12/17) utilized a check box format, 23% (4/17) utilized an open ended/fill in the blank format, and 6% (1/17) utilized a circle the response(s) format. Family history was inquired about in 82% (14/17) of forms and past medical history (PMH) in 58% (10/17) of forms. Gender questions were asked 82% (14/17) of the time for women, 29% (5/17) for men. Eighty‐eight percent (15/17) of forms had questions concerning any type of previous medication tried. Discussion: Patient intake forms are useful for clinical purposes, but vary markedly between UCNS headache centers. Ultimately, a universal intake form could be generated, providing a research‐based alternative to the form currently used at each center. Use of a standardized intake form by UCNS centers would streamline data collection, a good first step in the eventual generation of a headache registry.